OPTIMALISASI HUKUM DALAM PENDAYAGUNAAN ZAKAT PRODUKTIF (STUDI KASUS BAZNAS KABUPATEN PEKALONGAN) - Nada, Qothrun; Jumailah, Jumailah; Sa'adah, Novita Nurus (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
The aim of this research is to find out how optimization the law is for utilizing productive zakat according to Law no. 23 of 2011, PMA no. 52 of 2014, and PERBAZNAS No. 3 of 2018 as well as the factors underlying the effectiveness of the law for utilizing productive zakat in BAZNAS Pekalongan Regency.The research method used in this research is a descriptive qualitative empirical legal research method, the data source used is primary data in the form of interviews with BAZNAS administrators in Pekalongan Regency, and secondary data in the form of Law no. 23 of 2011, PMA no. 52 of 2014, PERBAZNAS No. 3 of 2018 and journal literature. Researchers analyzed the collected data using descriptive analysis methods. The results of this research indicate that the distribution and utilization of productive zakat by BAZNAS Pekalongan Regency is good according to interviews conducted with BAZNAS and Mustahik staff in accordance with Law no. 23 of 2011, PERMA no. 52 of 2014, and PERBAZNAS No. 3 of 2018 and BAZNAS Pekalongan Regency always enforce sanctions in the form of revoking zakat assistance to mustahik who violate the provisions. The results of the analysis show that the use of productive zakat is in accordance with the aim of productive zakat where mustahik earn additional income so they can spend and give away part of their income. However, awareness of the need to donate and give alms is still low. Therefore, based on the theory of legal effectiveness, it is known that Law no. 23 of 2011, PMA no. 52 of 2014, and PERBAZNAS No. 3 of 2018 can be said to be quite effective in BAZNAS Pekalongan Regency.